Fabrication of Polylactic Acid/β-Tricalcium Phosphate FDM 3D Printing Fiber to Enhance Osteoblastic-Like Cell Performance - Salamanca, Eisner; Tsao, Ting-Chia; Hseuh, Hao-Wen; Wu, Yi-Fan; Choy, Cheuk-Sing; Lin, Chin-Kai; Pan, Yu-Hwa; Teng, Nai-Chia; Huang, Mao-Chuan; Lin, Shang-Ming; Chang, Wei-Jen (Frontiers in Materials, 2021)
Guided-bone regeneration (GBR) is increasingly using 3-dimensional (3D) printing by fused deposition modeling (FDM) to build the filaments used for treatment. Polylactic acid (PLA) and beta-tricalcium phosphate (β-TCP) are widely used as base materials in 3D printing, necessitating that they are studied together in the context of GBR treatment. This study sought to test and compared the properties and efficacy of different ratios of β-TCP and PLA used to make 3D printed filament material to find the most effective combination of materials for GTR treatments. Several ratios of PLA to β-TCP were tested, including PLA/β-TCP ratios of 95%/5% (PLA-5), 90%/10% (PLA-10), % 85%/15% (PLA-15), and 80%/20% (PLA-20) and quantitative real-time polymerase chain reaction (QPCR) in vitro testing was done to characterize the material. After adding β-TCP to PLA, mechanical testing indicated that tensile and elongation strengths decreased, hardness was retained, and cell proliferation was promoted. The effect of PLA and β-TCP on increasing alkaline phosphatase (ALP) activity was significantly greater in a ratio of 10% β-TCP/90% PLA at 5 days (P <.05) than in any other ratio tested. This is supported by results from qPCR testing, which showed early osteoblast-like differentiation of DLX5, RUNX2, OPG, OC, and collagen type 1 (COL-1) expression levels similar to cells cultured on PLA-10. Our results demonstrated that 3D printing of filaments produced in a ratio of 90% PLA to 10% β-TCP was more effective for GBR than filaments produced using only PLA.